2017
DOI: 10.1002/tox.22509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypothalamus‐pituitary‐thyroid axis function by chronic perchlorate exposure in male rats

Abstract: Perchlorate is a widespread endocrine disruptor that was previously correlated with increased serum TSH levels and decreased thyroid hormones production both in animals and humans. Even so, the regulation of gene/protein expression in the hypothalamus, pituitary and thyroid by chronic perchlorate exposure was not completely elucidated. Therefore, this study aimed to investigate the underlying mechanisms involved in the disruption of hypothalamus-pituitary-thyroid axis by chronic perchlorate exposure. Male Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 71 publications
(75 reference statements)
1
0
0
Order By: Relevance
“…Alterations in thyroid hormone level are one of the important indicators when thyroid function changes in the body. In the present study we found that dams exposed to NP during perinatal period demonstrated decreased serum levels of FT3, FT4 in F1 male rats, which was consistent with previous study on the thyroid toxicity of endocrine disruptor (Serrano-Nascimento et al, 2018). These findings show that NP could lead to the hypoactivity of the thyroid gland.…”
Section: Discussionsupporting
confidence: 93%
“…Alterations in thyroid hormone level are one of the important indicators when thyroid function changes in the body. In the present study we found that dams exposed to NP during perinatal period demonstrated decreased serum levels of FT3, FT4 in F1 male rats, which was consistent with previous study on the thyroid toxicity of endocrine disruptor (Serrano-Nascimento et al, 2018). These findings show that NP could lead to the hypoactivity of the thyroid gland.…”
Section: Discussionsupporting
confidence: 93%